The Riksdag's open data - Debates - Rødven-Eide, Stian (University of Gothenburg, 2024)
A static dataset containing all debates from the Swedish parliament in the period 1993/94-2017/18. Some improvment on the source data has been done; for more information, see Anföranden: Annotated and Augmented Parliamentary Debates from Sweden.

En statisk datamängd bestående av alla riksdagens anföranden från och med riksmötet 1993/94 till och med riksmötet 2017/2018. Vissa förbättringar av källdatan har gjorts; för mer information, se Anföranden: Annotated and Augmented Parliamentary Debates from Sweden.
Riksdagens öppna data: Anföranden
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik